Correlation of Family Disharmony with Student Achievement in Islamic Education Lessons at SMP NUHA Banjarharjo Brebes - Muhammad Muslih (Edunesia : Jurnal Ilmiah Pendidikan, 2021)
Family harmony is one of the important factors in helping student achievement, because many students are raised in less harmonious families. The education and economy of their parents are relatively low, and they are also busy with making a living, all of which causes children's learning achievement to decline, especially in Islamic Religious Education lessons. This study aims to obtain data on the level of family disharmony of students at SMP NUHA Banjarharjo Brebes, in order to determine student achievement in Islamic Religious Education subjects and determine the relationship between family disharmony and student learning outcomes in Islamic Religious Education lessons at SMP NUHA Banjarharjo Brebes. The method used by the researcher is field research to collect data by observation, documentation, interviews, and questionnaires. Information that is qualitative is replaced with quantitative information with the technique of giving a value to all alternative answers. The results showed that the level of family disharmony of the students of SMP NUHA Banjarharjo Brebes was at a moderate level, the conclusion from the average value of student participants in Islamic religious learning was classified as moderate, and the correlation between students' family disharmony and student learning outcomes in Islamic Religious Education was classified as strong 0.77.